Synergistic effects of Rahnella aquatilis and Trichoderma orientale in biocontrol of common bacterial blight in bean - Nashwa M. A. Sallam; Munirah F. Aldayel (Egyptian Journal of Biological Pest Control, 2025)
Abstract Background Common bacterial blight, caused by Xanthomonas axonopodis pv. phaseoli (Xap), is a major disease affecting bean plants. While biocontrol agents have been explored to manage plant diseases, there is limited research on the combined use of multiple agents for controlling bean bacterial blight. This study aimed to evaluate the efficacy of the bacterium Rahnella aquatilis (Ra) and the fungus Trichoderma orientale (TO), used singly or in combination, in protecting bean plants against this disease. Results In in vitro experiments, R. aquatilis and T. orientale strongly inhibited Xap growth and exhibited significant zinc and phosphate solubilization abilities. Under greenhouse conditions, treatments with Ra, TO, or their combination significantly suppressed disease incidence, achieving reductions of 69, 56, and 70%, respectively. Both biocontrol agents decreased the pathogen load in bean leaf tissues and improved seed germination rates, which reached 92 and 82% for Ra and TO, respectively, compared to 67% in the infected control. Additionally, treated bean plants showed increased fresh and dry weights of roots and shoots compared to untreated plants. Conclusion This study demonstrates that the combined application of R. aquatilis and T. orientale is an effective eco-friendly strategy for controlling common bacterial blight in beans. These biocontrol agents synergistically reduced disease severity, enhanced plant growth, and improved seed germination, emphasizing their utility in sustainable agriculture.